(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Some people refer to cortisol as the stress hormone. The body produces cortisol to prepare the body to respond to a perceived danger or stressful situation. When facing sudden stress, the body enters an alarm reaction stage called the fight-or-flight response. This triggers a cascade of events to enable a person to act quickly. Stress raises the cortisol level in the body, triggering bodily changes that enable a person to react to the stressor.